Aeroelastic modelling and analyses of a short wing-propeller configuration - Wang, Zi (2021)
Rotorcraft designs with the ability to fly as an aircraft but take off and land vertically as helicopters were first introduced in the early 1950s. However, the development of such concept stopped after a few failed attempts. Similar configurations, in which wings are equipped with additional propulsive propellers, has re-emerged in the past ten years for the compound helicopter and tilt-rotor aircraft. Those designs are aimed at introducing a new way of providing propulsive thrust, increasing the cruise speed, while retaining hovering advantages. However, the still open issue of high level of vibration resulting from fluid-structure interaction is exacerbated in the case of those rotorcrafts, with even more critical effects on the fatigue life, maintenance costs, on-board instrumental efficiency and comfort. Being able to model and predict the complex aeroelastic behaviour associated with the wing-propeller system is extremely important for achieving an optimised design. This project is an initial attempt to apply comprehensive analysis onto such compound aero-structures. Aiming at providing sufficient information of dynamic responses in the time-domain for the preliminary design stages, low-fidelity aeroelastic models are reviewed and basic structural and aerodynamic theories are introduced as basic building blocks.